Dynamics of the development of the epidemic of coronavirus infection and assessment of population immunity to SARS-COV-2 in the territory of the Kyrgyz Republic - Zhanylai N. Nuridinova; Zuridin Sh. Nurmatov; Tatyana E. Kuchuk; Kaliya K. Kasymbekova (Heart Vessels and Transplantation, 2024)
Objective: The aim of this study was to assess the dynamics of the development of the coronavirus infection epidemic and their relationship with the formation of population immunity to the SARS-CoV-2 virus among the population of the Kyrgyz Republic.